Krüppel-like Factor 4 is Required for the Expression of Vascular Smooth Muscle Cell Differentiation Marker Genes Induced by All-Trans Retinoic Acid - Wang, Chao; Han, Mei; Zhao, Xin-Ming; Wen, Jin-Kun (Journal of biochemistry (Tokyo), 2008)
Krüppel-like factor 4 (KLF4) is involved in phenotypic modulation of vascular smooth muscle cells (VSMCs). All-trans retinoic acid (ATRA) inhibits VSMC proliferation and induces VSMC differentiation. However, the role of KLF4 in ATRA-elicited VSMC phenotypic modulation remains unclear. Here, we show that treatment of VSMCs with ATRA resulted in significant inhibition of proliferation and migration of VSMCs, as well as up-regulation of KLF4 and the VSMC differentiation marker genes SM22α and SM α-actin (α-SMA). At the same time, the KLF4 target gene p53 was up-regulated, while the VSMC dedifferentiation marker gene nonmuscle myosin heavy chain-B (SMemb) was down-regulated. We also show that overexpression of KLF4 in VSMCs increased the expression of p53, SM22α and α-SMA, but decreased the expression of SMemb and VSMC proliferation and migration. Silencing of KLF4 expression by KLF4-specific small interfering RNA (siRNA) abrogated the inducing effects of ATRA on p53, SM22α and α-SMA expression and neutralized the inhibitory effects of ATRA on SMemb expression and VSMC proliferation and migration. Thus, our data suggest that KLF4 is required for the expression of VSMC differentiation marker genes induced by ATRA and that this transcription factor is one of the key mediators of retinoid actions in VSMCs.